1992
DOI: 10.1037/0022-006x.60.5.783
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early adolescent disorder from childhood aggression and peer rejection.

Abstract: Two large cohorts of Black 3rd-grade children from low-income families were followed into early adolescence. Adjustment at the end of the 1st year of middle school was assessed by teacher and parent ratings and by adolescent self-reports. Childhood peer social status predicted parent-reported externalized and internalized disorder and self-reported internalized disorder. Childhood aggression predicted self-reported externalized and internalized disorder and parent-reported externalized disorder. Teacher rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
244
2
11

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(270 citation statements)
references
References 21 publications
13
244
2
11
Order By: Relevance
“…The link between rejection at school and development of psychological problems such as depression and stress has been well established in studies both using cross-sectional (Coie, Lochman, Terry, & Hyman, 1992) and longitudinal designs (Kiesner, 2002;Kiesner, Poulin, & Nicotra, 2003), both for aggressive and nonaggressive rejected students (Hecht, Inderbitzen, & Bukowski, 1998); however, nonaggressive rejected students usually obtain higher scores in measures of loneliness, shyness, and worries about being rejected again compared to aggressive rejected students (Parkhurst & Asher, 1992).…”
Section: Personal Variablesmentioning
confidence: 99%
“…The link between rejection at school and development of psychological problems such as depression and stress has been well established in studies both using cross-sectional (Coie, Lochman, Terry, & Hyman, 1992) and longitudinal designs (Kiesner, 2002;Kiesner, Poulin, & Nicotra, 2003), both for aggressive and nonaggressive rejected students (Hecht, Inderbitzen, & Bukowski, 1998); however, nonaggressive rejected students usually obtain higher scores in measures of loneliness, shyness, and worries about being rejected again compared to aggressive rejected students (Parkhurst & Asher, 1992).…”
Section: Personal Variablesmentioning
confidence: 99%
“…Ladd concluded that "the types of relationships children form with peers in the classroom function as a source of stress or support and shape the course of early school adaptation" (p. 1082). Other researchers have documented the buffering effect of peer support (both friendship and peer acceptance) for children experiencing a range of stressors (Coie et al, 1992;Ladd & Kochenderfer, 1996;Masten & Coatsworth, 1998).…”
Section: Developmental Consequences Of Peer Relatednessmentioning
confidence: 99%
“…The scores were standardized by classroom and gender (Coie et al, 1992;Zakriski & Coie, 1996). This cut-off strategy is quite restrictive and ensures that those classified as 'aggressive' in the present study were indeed those who obtained the highest scores on this behavioral measure (Cava, 2011;Cava, Buelga, Musitu, & Herrero, 2011).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Thus, social rejection has been associated with indicators of maladjustment such as anxiety, stress, presence of depressive symptoms (Coie, Lochman, Terry, & Hyman, 1992;Estévez, Herrero et al, 2006;Kiesner, 2002), feelings of loneliness, and low satisfaction with life (Hay, Payne, & Chadwick, 2004;Woodward & Fergusson, 1999). Rejected adolescents, compared to their popular peers, perceive themselves as socially less capable and have less positive expectations of social success, so they make fewer attempts to establish social interactions and, as a consequence, they are at greater risk of developing severe social isolation which in turn contributes to their emotional impairment .…”
Section: Intra-individual Levelmentioning
confidence: 99%